Malignant mesothelioma: attributable risk of asbestos exposure. Issue 12 (December 1994) - Spirtas, R; Heineman, E F; Bernstein, L; Beebe, G W; Keehn, R J; Stark, A; Harlow, B L; Benichou, J
Abstract : OBJECTIVES--To evaluate a case-control study of malignant mesothelioma through patterns of exposure to asbestos based upon information from telephone interviews with next of kin. METHODS--Potential cases, identified from medical files and death certificates, included all people diagnosed with malignant mesothelioma and registered during 1975-1980 by the Los Angeles County Cancer Surveillance Program, the New York State Cancer Registry (excluding New York City), and 39 large Veterans Administration hospitals. Cases whose diagnosis was confirmed in a special pathology review as definite or probable mesothelioma (n = 208) were included in the analysis. Controls (n = 533) had died of other causes, excluding cancer, respiratory disease, suicide, or violence. Direct exposure to asbestos was determined from responses to three types of questions: specific queries as to any exposure to asbestos; occupational or non-vocational participation in any of nine specific activities thought to entail exposure to asbestos; and analysis of life-time work histories. Indirect exposures were assessed through residential histories and reported contact with family members exposed to asbestos. RESULTS--Among men with pleural mesothelioma the attributable risk (AR) for exposure to asbestos was 88% (95% confidence interval (95% CI) 76-95%). For men, the AR of peritoneal cancer was 58% (95% CI 20-89%). For women (both sites combined), the AR was 23% (95% CI 3-72%). The large differences in AR by sex are compatible with the explanations: a lower background incidence rate in women, lower exposure to asbestos, and greater misclassification among women. CONCLUSIONS--Most of the pleural and peritoneal mesotheliomas in the men studied were attributable to exposure to asbestos. The situation in women was less definitive.